2000
DOI: 10.1212/wnl.55.3.429
|View full text |Cite
|
Sign up to set email alerts
|

Nonconvulsive focal inhibitory seizure: Subdural recording from motor cortex

Abstract: The authors obtained an ictal electrocorticogram with chronically implanted subdural electrodes from a 30-year-old man with a low grade glioma in the right postcentral gyrus who had a focal inhibitory seizure of the left arm. During the ictal paresis, the authors observed epileptic discharges in the positive arm motor area of the right precentral gyrus and in its rostral area, but not in the negative motor area. The epileptic activity probably inhibited the spinal motoneuron pool without eliciting excitatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 8 publications
(7 reference statements)
0
30
1
2
Order By: Relevance
“…32) A total of 23 cases of intraparenchymal meningiomas have been reported including the present case (Table 1). 4,5,[10][11][12][13][14][15][16][18][19][20][24][25][26][27][28][29]31,32) Eighteen patients were aged from 0 to 19 years, and 15 were aged 14 years or younger, so the incidence of pediatric intraparenchymal meningioma is higher than adults. There were 10 males and 10 females, but 8 males and 5 females were aged from 0 to 14 years, indicating male predominance.…”
Section: Discussionmentioning
confidence: 99%
“…32) A total of 23 cases of intraparenchymal meningiomas have been reported including the present case (Table 1). 4,5,[10][11][12][13][14][15][16][18][19][20][24][25][26][27][28][29]31,32) Eighteen patients were aged from 0 to 19 years, and 15 were aged 14 years or younger, so the incidence of pediatric intraparenchymal meningioma is higher than adults. There were 10 males and 10 females, but 8 males and 5 females were aged from 0 to 14 years, indicating male predominance.…”
Section: Discussionmentioning
confidence: 99%
“…The EMG silent period starts 20 to 40 ms after the preceding EEG transient such as spikes or spike‐and‐wave complex, and generally lasts ∼200 ms, or ≤400 ms in some cases. Matsumoto et al (19) reported a case of focal inhibitory seizure whose pathophysiology was explained by epileptic discharges originating from a part of the primary motor area (M1), as demonstrated by subdural electrodes. In this patient, sustained focal inhibitory seizure was explained by successive EMG silent periods after repetitive 2‐ to 3‐Hz epileptic activity at M1.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] We previously reported the findings of electrocorticographic (ECoG) recording during ictal monoparesis of an arm, which demonstrated ictal discharges in the contralateral primary arm motor area (arm MI). 6 So far, we have had a total of three patients with ictal monoparesis of the arm. The well-circumscribed lesion commonly observed in the primary arm somatosensory area (arm SI) drew our attention to report this case series with an emphasis on the role of SI lesion in generation of the ictal monoparesis.…”
mentioning
confidence: 99%
“…(D) T2-weighted image of Patient 3.A well-demarcated highintensity lesion, consistent with a lowgrade glioma, is seen in the right postcentral gyrus. Another MRI with different scan sequence appeared elsewhere 6. …”
mentioning
confidence: 99%